Is less more? Experimenting with visual stacking of coincident maps for spatial global sensitivity analysis in urban land-use change modeling. (November 2021) - Şalap-Ayça, Seda; Jankowski, Piotr; Clarke, Keith C.; Nara, Atsushi
Abstract: Visualization of the outputs from sensitivity analyses of spatially explicit models can potentially enhance the perception of the uncertainty in model outputs. However, spatial global sensitivity analysis (GSA) produces multiple output maps, twice as many as the number of input parameters under investigation, which can result in an overwhelming visual load to interpret. In this research, we tested the visual stacking of coincident maps to handle the visual complexity for an application of an urban land-use change model. The coincident maps were compared with the adjacent representation. Both types of maps were tested using a web-based survey to understand the efficacy in supporting the comprehension of the GSA results. The majority of the questions showed no statistically significant difference between visualization techniques; however, the difficulty of interpreting the adjacent maps was observed among novice users which suggesting the need for an update for the future representations using coincident maps. Highlights: Spatial GSA produces multiple output maps, and the number increases proportionally with the increase of input parameters. We illustrate a new visual stacking representation which summarizes several GSA attributes for the same location. The new technique was tested against the most commonly used spatial visualization technique applied for GSA.